Analysis of the family functionality and its relationship with the quality of life of the families of a marginal urban district of the city of Quito, february to september 2014 (Horizontes de Enfermería, 2018)
The present research studies the relationship between Family Functioning Effectiveness and the Health Related Quality of Life of families in an urban slum in the city of Quito. In order to achieve the objectives, information on family functioning was systematized, the dimensions of the family system, such as system maintenance, system change, cohesion, and individuation of families and goals of the family system are described: control, stability, growth, spirituality of families, which are considered mainstays in determining family functioning. Following the data collection and their analysis, it is concluded that the effectiveness of family functionality evidence low levels and comprising at 83.33% of all families in the study. Only 16.67% of all households reach an average level of effectiveness in family functioning, and 0% of families are located in a high level of effectiveness in family functioning. The effectiveness of family functioning is related positively or negatively to the dimensions of physical and mental health. It was also found that the level of the effectiveness of family functionality does not exceed the 55 points corresponding to an intermediate level
Keywords: Family Functionality Effectiveness; Health related Quality of Life; dimensions of the family system; cohesion and individuation of families; family system goals; control; growth; stability; spirituality